KURIKULUM MADRASAH ALIYAH NEGERI 2 POLEWALI MANDAR PRESPEKTIF MANAJEMEN MUTU SEKOLAH - Hirma, Hirma (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2022)
This research is aimed at decrypting the country's 2 polewali mandar's madrassa curriculum. The study USES a type of qualitative research with an approach to case studies. The object of this study was performed at the man 2 polman. Data collection techniques use observation, interviews, and documentation. The data sources in this study include the headmaster, the vice principal of curriculum, students, committee and students. The analysis techniques used in the study are data collecting, data reduction, data presentation, deduction. The triangulation used to test the validity of data is source triangulation. Based on research results from 4 standards contained 4 principles: 1. The standards of graduate competence are reviewed: a) customer satisfaction, parental involvement in SKL formulations, b) leadership as well as school involvement in SKL, c) teamwork, teamwork between teachers in formulating SKL. D) the measurement, the evaluation of the student's value 2. The content standard is reviewed: a) customer satisfaction, mastering and explaining lesson materials,b) leadership, principal involved in prgram c production) teamwork, involvement, school fads, board of teachers, committee, and education services (d) measurements, the quantification of the 3 prepared programs. Process standards covered: A) customer satisfaction, to achieve the goal of learning by making learning syllabus b) leadership, the principal does silabus creating guidance and development. C) teamwork, teamwork in the formulation of preliminary activities, core activities down to the conclusion of the d) measurement, that is, the evaluation of the learning process, the performance of the learning process, the assessment of the learning process and the monitoring of the learning process. 4. The standard of assessment is reviewed: a) customer assessments of students who include attitude, knowledge, and skill b) leadership, the headmaster conducting a joint evaluation c) teamwork of teachers in formulating materials, designing learning activities, developing learning activities, adding lesson materials, d) measurement, took place at the time of the implementation of the study plan (RPP) based on the syllabus